The Results of Experimental Studies on the Determination of the Optimal Values of the Parameters of Levels Mounted on Vegetable Seeding Machine - Tukhtakuziev Abdusalim; Ibragimov Abdirasuli Abdikarimovich; Khamidov Nurmukhammad Muxtarovich; Eshdavlatov Akmal Eshpulatovich (Genius Journals, 2022)
It is presented in the article that, the parameters of the levers to be installed in the horizontal furrow, which form a lump of comb maker, and which line the seeds of small seed vegetable crops to the top, that is, the height of their installation in comb maker, the direction of movement and the angle of installation in relation to the steep, as well as the geometrical dimensions of the the results of the multi-factor experimental studies on the determination of the optimal values that the case provides
Keywords: Vegetable seeding machine; comb maker; alignment installed on the power; height of alignment installations on the pusher